2016
DOI: 10.1007/s13277-016-5310-9
|View full text |Cite
|
Sign up to set email alerts
|

MiR-429 is linked to metastasis and poor prognosis in renal cell carcinoma by affecting epithelial-mesenchymal transition

Abstract: MicroRNAs (miRNAs) have been proven to be important oncogenes and tumor suppressors in wide range of cancers, including renal cell carcinoma (RCC). In our study, we evaluated miRNA-429 as potential diagnostic/prognostic biomarker in 172 clear cell RCC patients and as a potential regulator of epithelial-mesenchymal transition (EMT) in vitro. We demonstrated that miR-429 is down-regulated in tumor tissue samples (P < 0.0001) and is significantly associated with cancer metastasis (P < 0.0001), shorter disease-fre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
24
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 29 publications
0
24
1
1
Order By: Relevance
“…MicroRNA expression patterns have been reported to be more accurate in establishing the right diagnosis than the mRNA criteria, in poorly differentiated metastatic cancer cases with cancer of unknown primary origin (45). In ccRCC, miRNA-429 was found to be a potential diagnostic and prognostic biomarker and a potential regulator of EMT(46). miR-429 was significantly associated with cancer metastasis, shorter disease-free and overall survival(46).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MicroRNA expression patterns have been reported to be more accurate in establishing the right diagnosis than the mRNA criteria, in poorly differentiated metastatic cancer cases with cancer of unknown primary origin (45). In ccRCC, miRNA-429 was found to be a potential diagnostic and prognostic biomarker and a potential regulator of EMT(46). miR-429 was significantly associated with cancer metastasis, shorter disease-free and overall survival(46).…”
Section: Discussionmentioning
confidence: 99%
“…In ccRCC, miRNA-429 was found to be a potential diagnostic and prognostic biomarker and a potential regulator of EMT(46). miR-429 was significantly associated with cancer metastasis, shorter disease-free and overall survival(46). Our results reveal that miR-720 expression can robustly (p<0.0001) discriminate malignant from non-malignant tissues and hence can be used as a diagnostic marker for RCC.…”
Section: Discussionmentioning
confidence: 99%
“…However, the role of miR-429 is controversial. Machackova et al reported that miR-429 acts as a tumor suppressor by inhibiting the loss of E-cadherin in RCC cells (23). miR-429 can also inhibit the migration, invasion, and proliferation of RCC cells by targeting Sp1 directly (15).…”
Section: Discussionmentioning
confidence: 99%
“…Zinc finger E‐box binding homeobox 1 and Crk‐like have also been identified as direct target responsible for the inhibitory effect of miR‐429 on cell migration and invasion in breast cancer cells . MiR‐429 is aberrantly downregulated in renal cell carcinoma and associated with longer patients' survival . Furthermore, the antitumour effect of miR‐429 on gastric carcinoma cells, cervical cancer cells and bladder cancer cells have also been documented.…”
Section: Discussionmentioning
confidence: 99%
“…41 MiR-429 is aberrantly downregulated in renal cell carcinoma and associated with longer patients' survival. 42 Furthermore, the antitumour effect of miR-429 on gastric carcinoma cells, 43 cervical cancer cells 44 and bladder cancer FIGURE 5 SOX2 mediates the antitumour effect of miR-429 in GBM cells. A, SOX2 expression is successfully restored in GBM cells.…”
Section: Discussionmentioning
confidence: 99%